2019
DOI: 10.1097/dbp.0000000000000666
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Care Demands Among Primary Caregivers of Young Children with Evidence of Congenital Zika Virus Infection in Brazil

Abstract: Objective-Evidence suggests that caring for a child with special health care needs can affect many domains of family life, including caregiver mental health. However, few studies have examined these outcomes among families impacted by the Zika virus (ZIKV). This study examines depressive symptom severity and care demands among primary caregivers of children, aged 15 to 26 months, with evidence of congenital Zika virus infection (ZVI).Methods-A sample of primary caregivers of children with evidence of congenita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 26 publications
(45 reference statements)
1
25
0
9
Order By: Relevance
“…M16 reported feeling greater sadness caused by her family's miserable living conditions than her daughter's diagnosis of microcephaly associated with CZS. This reflects the results of a study reporting that primary caregivers of children with CZS present depressive symptoms when faced with economic challenges related to the child's delayed development . In other words, economic challenges have a greater influence on the mental health of primary caregivers than the daily care of the child.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…M16 reported feeling greater sadness caused by her family's miserable living conditions than her daughter's diagnosis of microcephaly associated with CZS. This reflects the results of a study reporting that primary caregivers of children with CZS present depressive symptoms when faced with economic challenges related to the child's delayed development . In other words, economic challenges have a greater influence on the mental health of primary caregivers than the daily care of the child.…”
Section: Discussionsupporting
confidence: 63%
“…It is important to recognize that abortion is illegal in Brazil and families of low socioeconomic status face the greatest challenges in raising a disabled child. Furthermore, reproductive decisions are intimately related to personal convictions and cultural beliefs and are embedded in sociocultural norms …”
Section: Discussionmentioning
confidence: 99%
“…These results were expected because uncertainties and feelings of worrisome were detected during pregnancy, but when mothers delivered a healthy baby, their emotional state improved as feelings of worrisome decreased. In the long term, this low perception of risk could be a problem leading to lower attendance to medical visits and under-detection of neurodevelopmental disabilities, because healthy-at-birth infants born to mothers with confirmed ZIKV infection still need long-term follow up to detect neurodevelopmental delays [ 7 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The greater part of the affected populations lives in constraint-resource settings where making the most out of available resources is a major challenge [ 11 ]. Caregivers of children with disabilities are a group particularly susceptible to developing poor mental health, including depression, anxiety, and stress [ 12 , 13 ]. Furthermore, they might suffer an intensification of emotional symptoms, and also unhealthier habits, due to delays in children’s neurodevelopment over the years [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we measured the frequencies of IL-6+ cells within each of these populations, as it has been reported that IL-6 is upregulated during ZIKV infection (45). We found no significant differences in the frequencies of IL-6+ CD45+, IL-6+ CD68+, IL-6+ CD11b+, IL-6+ CD11c+, IL-6+ Ly6C+, or IL-6+ CD103+ cells between groups ( Fig.…”
Section: Resultsmentioning
confidence: 99%